Isolation of bacteriophages from surface waters specific for Shigella dysenteriae and their characterization as potential biocontrol agents - Mubarak, Ayesha (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.